Effects of burn severity on organic nitrogen and carbon chemistry in high-elevation forest soils - Holly K. Roth; Amy M. McKenna; Myrna J. Simpson; Huan Chen; Nivetha Srikanthan; Timothy S. Fegel; Amelia R. Nelson; Charles C. Rhoades; Michael J. Wilkins; Thomas Borch (Elsevier, 2023)
Fire frequency and severity have increased in recent decades in the western United States, with direct implications for the quantity and composition of soil organic matter (SOM). While the effects of wildfire on soil carbon (C) and inorganic nitrogen (N) have been well studied, little is known about its impacts on soil organic N. Since organic N is the most abundant form of soil N in conifer forests and dominant source of plant N facilitated by symbiotic mycorrhizae and mineralization, better understanding of post-fire organic N chemistry will help address a critical gap in our understanding of fire effects on SOM. Here, we characterized changes to organic N chemistry across fire severity gradients resulting from two wildfires that burned lodgepole pine (Pinus contorta) forest along the Colorado/Wyoming border, USA. One representative gradient was selected for high-resolution analysis based on results from bulk data (total C and N, and pH). Mineral soils were collected from two depths in low, moderate, and high severity burned areas and adjacent, unburned locations one year following the Ryan and Badger Creek fires. Nuclear magnetic resonance spectroscopy and 21 tesla ultrahigh-resolution Fourier transform ion cyclotron resonance mass spectrometry analysis showed that N content and aromaticity of water-extractable SOM (0-5 ​cm depth) increased with burn severity, while minimal changes to 5-10 ​cm depth were observed. Heterocyclic N species are generally higher in toxicity compared to their non-nitrogenated counterparts, which prompted soil toxicity measurements. Complementary Microtox® analysis revealed a positive relationship between increased fire severity and increased soil toxicity to Aliivibrio fischeri (microbial test species). These findings add to our molecular-level understanding of organic C and N responses to wildfire severity, with likely implications for nutrient cycling, forest recovery and water quality following severe wildfire.